EDUKASI POLA PENGASUHAN DALAM MENINGKATKAN PENGETAHUAN ORANGTUA SEBAGAI UPAYA PENCEGAHAN STUNTING - Rini Harianti; Julinda Zahrani Pratopo (JOMIS (Journal of Midwifery Science), 2026)
Introduction: Stunting, which is defined as height below the age standard as a result of persistent malnutrition, is a sign of long-term growth failure in children. West Java had the greatest percentage of stunting, according to the 2023 Indonesian Nutritional Status Survey (SSGI). The prevalence rose from 14% in 2022 to 17% in 2023 in Karawang Regency. Given the significance of the first 1000 HPK, parental understanding of caregiving practices is essential to the effectiveness of interventions. Objective: To prevent stunting in the working area of Puskesmas Rengasdengklok, Karawang, this research aims to enhance parents' knowledge regarding parenting patterns through parental education. Methods: This study uses a quasi-experimental design with a one-group pretest and posttest. The total sampling technique was used to select 16 mothers' biological mothers (primary caregivers) of toddlers aged 12-36 months, permanent residents, and possessing adequate communication and literacy skills. Data were collected using a structured questionnaire instrument. The difference before and after the intervention was measured through statistical analysis using the Shapiro-Wilk test and the paired t-test at a significance level of α=0.05. Results: The majority of respondents were in age range of 20-40 years and had a background of elementary school (56.3%). The results showed changes in the cognitive domain of mothers: initially, 62.5% of respondents were in the category of low knowledge, which became 0% after the intervention, and 68.8% were in the category of good knowledge, significantly increasing (p=0.019). The average knowledge score increased from 4.38 to 7.00. The education provided was very effective for mothers with elementary education as preventive action. Recommendation: Parents should maximize the golden period of 1000 HPK by maintaining balanced nutrition and regularly monitoring the growth of toddlers.